2020
DOI: 10.3390/met10111479
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Grain Height Characteristics of Electroplated cBN Grinding-Wheel Active Surfaces Associated with Their Wear

Abstract: During the operation of a single-layer grinding wheel (SLGW), irreversible changes occur on its active surface due to wear. The study of grinding-wheel microgeometry changes can be based on the measurement of the surface texture as well as the determination and analysis of its parameters. The article deals with the selection of suitable texture parameters and an appropriate mathematical model carrying information about the SLGW condition. In the study, samples of Pyrowear 53 steel were ground using electroplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 43 publications
4
14
0
Order By: Relevance
“…More examples concerning the application of the proposed methodology of determining the cut-off level and segmentation of grains, areas of sticking, and pores on a GWAS in the context of grinding wheel performance are presented in [69]. That paper describes the results of research related to determination of GWAS parameters that are particularly sensitive to wear, including the parameters of grains, areas of sticking, and pores segmented using the developed methodology.…”
Section: The Results Of the Grinding Wheel Topography Tests During The Service Lifementioning
confidence: 99%
“…More examples concerning the application of the proposed methodology of determining the cut-off level and segmentation of grains, areas of sticking, and pores on a GWAS in the context of grinding wheel performance are presented in [69]. That paper describes the results of research related to determination of GWAS parameters that are particularly sensitive to wear, including the parameters of grains, areas of sticking, and pores segmented using the developed methodology.…”
Section: The Results Of the Grinding Wheel Topography Tests During The Service Lifementioning
confidence: 99%
“…With an increase in the feed rate, the grinding efficiency and the undeformed chip thickness, both being are a measure of the load on the grinding wheel -thus, the grinding force and power components also increase. This, in turn, is associated with increased wear of the grinding wheel [23,24]. However, the analysis of variance did not show any significant dependencies between the feed rate and the wear of grinding wheels (observed through the parameters Sa and Ŝz from the active surface of the grinding wheel (Fig.…”
Section: Influence Of Feed Rate On the Wear Of Grinding Wheel Cutting Surfacementioning
confidence: 91%
“…Following the initial transient wear, where pullout and fracturing dominate, steady-state wear evolution is reached, during which attritious wear causes dulling of the abrasive grain tips and formation of smooth wear flats along with striation marks in the grinding direction, and progressively increasing number of active grains as the most protruding grains wear down [7,10]. It is reported that the wear behavior of electroplated cBN grains is highly dependent on the properties of the abrasive grade, workpiece material, and process parameters with variations in the observed active mechanisms commonly observed, such as a reduced tendency for pullout [11] or reduced fracturing in some cases [12]. However, a common feature across all earlier work is the conclusion that the surface topography of the grinding wheel changes dramatically as a result of wear [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, as many as 144 surface texture parameters have previously been considered for assessing grinding wheels' condition [11]. These could be categorized into three groups of surface texture parameters, including height-based, hybrid, and functional parameters [11,[17][18][19] presented in Table 1 according to ISO 25178 [20].…”
Section: Introductionmentioning
confidence: 99%